2014
DOI: 10.3233/ch-141808
|View full text |Cite
|
Sign up to set email alerts
|

Lack of correlation between coronary blood flow and carotid intima media thickness

Abstract: BACKGROUND: The phenomenon of slow coronary flow (SCF) in the presence of normal coronary arteries may indicate endothelial dysfunction, which is characteristic of an early stage in the development of atherosclerosis. Measurement of the Carotid Intima-Media Thickness (CIMT) allows identification of early stages of atherosclerosis. CIMT might offer a non-invasive method of diagnosing SCF patients. Previous studies demonstrated conflicting results regarding the relationship between these two phenomena. In the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…The phenomenon of SCF in the presence of normal coronary arteries may indicate endothelial dysfunction, which is characteristic of an early stage in the development of atherosclerosis. Despite this association, such patients do not have increased carotid IMT values ( 50 ). In line with our results stands a study by Tabara et al including 1,978 participants from two independent cohorts, which showed that hematocrit was positively associated with insulin resistance and insulin sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…The phenomenon of SCF in the presence of normal coronary arteries may indicate endothelial dysfunction, which is characteristic of an early stage in the development of atherosclerosis. Despite this association, such patients do not have increased carotid IMT values ( 50 ). In line with our results stands a study by Tabara et al including 1,978 participants from two independent cohorts, which showed that hematocrit was positively associated with insulin resistance and insulin sensitivity.…”
Section: Discussionmentioning
confidence: 99%